Comparison of Two Sharia Insurance Unit-Linked Products Through Tabarru Fund Simulation - Yuyun Eka Pratiwi; Restu Ananda Putra; Novriana Sumarti (Program Studi Ilmu Komputer, Universitas Pakuan, 2025)
The number of sharia insurance products has been steadily increasing over the past few decades. According to some research, this rise is expected to reach 15–20%. Tabarru funds, which are gathered funds intended to support one another without payment, should be included in the sharia insurance policy. This fund is supposedly gathered to cover the insured person's claim. Additionally, sharia insurance providers provide unit-linked sharia insurance, which was first made available by traditional insurance providers. This paper explains the operation of unit-linked sharia insurance. We examine this product that is offered by many companies. We develop a mathematical model to compute the unit-linked product's tabarru fund and simulate a few scenarios. The outcome shows that some ujrah (fees), such as these for acquisition, administration, risk management, investment management, and fund transfers, are deducted from the contribution that was paid. The simulations involving a subject who lives to be 99 years old and dies at specific ages reveal differences in the quantity of tabarru funds gathered from the products under observation. The tabarru funds collected in products A and B are IDR 110.040.000 and 9.072.000, respectively. This amount is not enough to cover the promised claims.